The Application of Cytokine Expression Assays to Differentiate Active From Previously Treated Syphilis - Kojima, Noah (J Infect Dis, 2020)
To investigate the role of serum cytokine assays to distinguish between active from treated syphilis among serofast patients, we recruited individuals into a prospective cohort study. Participants underwent routine syphilis screening. We selected specimens from a majority cohort of serofast participants with treated and active syphilis. We analyzed specimens with a 62-cytokine multiplex bead-based enzyme-linked immunosorbent assay. Cytokines, brain-derived neurotrophic factor and tumor necrosis factor β, were most predictive. We built a decision tree that was 82.4% accurate, 100% (95% confidence interval, 82%–100%) sensitive, and 45% (18%–75%) specific. Our decision tree differentiated between serum specimens from serofast participants with treated syphilis versus active syphilis.